Development of Composition and Technology of Effervescent Tablets with Biologically Active Complex of Black Chokeberry (Aronia melanocarpa (Michx.) Elliott) Fruits - N. S. Pivovarova; O. N. Abrosimova; T. S. Shebitchenko; N. V. Sokrasnkina; A. A. Shmarova; E. K. Novikova; K. O. Sidorov (Разработка и регистрация лекарственных средств, 2022)
Introduction. Actual use of plant raw materials in the production of medicines is caused by a variety of bioactive substance complexes in their composition. These drugs have a wide range of therapeutic effects and in this regard, the properties and compositions of various plant materials are currently being actively studied. Aronia melanocarpa (chokeberry) has been the focus of scientific research for many years to identify various healing properties, and in 2015 its fresh and dried fruits are presented as a plant raw material in the State Pharmacopoeia of the Russian Federation, XIV edition. The variety of biologically active substance complexes of Aronia melanocarpa fruit allows its use in different fields (food and pharmaceutical industries). For this reason, the development of the composition and technology of effervescent tablets containing a complex of biologically active substances and possessing the following advantages: rapid release of active ingredients, high rate of BAS assimilation, usability and pleasant flavor are of interest.Aim. The aim of the present study is to develop the composition and technology of effervescent tablets with a biologically active complex from dried Аronia melanocarpa fruits.Materials and methods. Extracts enriched with anthocyanins were obtained from dried chokeberry fruits. As excipients in the technology of effervescent tablets, sodium carbonate, tartaric acid, lactose monohydrate, povidone (Plasdone™ K-29/32), polyethylene glycol 6000 and aspartame were used. Under laboratory conditions, granules (acidic and basic) were obtained by the method of punching wet masses, where extract (granulate 1) and ethyl alcohol 96 % (granulate 2) were used as a moisturizer. Numerical indicators of medicinal plant raw materials, technological properties of granulate and tableting mass, as well as quality indicators of effervescent tablets were determined according to the methods described in the State Pharmacopoeia of the Russian Federation, XIV edition.Results and discussion. Numerical indicators of dry fruits of Aronia melanocarpa (crushing of raw materials and the content of foreign impurities, total ash in plant raw materials and ash insoluble in hydrochloric acid, content of extractives) were determined, and the good quality of the raw materials used in the subsequent stages of drug development was confirmed. An extract enriched with anthocyanins has been developed. The composition and technology of effervescent tablets with separate granulation of acidic and basic components has been developed. Extract and ethyl alcohol 96 % were used as moisturizers, and aspartame was used to improve taste characteristics. A draft specification for the quality indicators of effervescent tablets based on enriched extraction has been proposed.Conclusion. In the course of the research work, the numerical indicators of medicinal plant raw materials were determined and its quality was confirmed, which enabled its use for further extraction. Extraction conditions were chosen, extracts were obtained. Excipients have been selected, the composition and technology of effervescent tablets based on the extracts of Aronia melanocarpa fruits have been developed, a draft specification for effervescent tablets has been proposed in accordance with the requirements of the State Pharmacopoeia of the Russian Federation, XIV edition.